Sosialisasi Anti Bullying melalui Program Kuliah Kerja Nyata sebagai Upaya Pencegahan Perundungan di Sekolah Dasar - Kharirotus Saadah (Jurnal Inovasi Pengabdian Masyarakat, 2026)
Bullying in elementary school environments is a serious issue that can negatively affect students’ psychological, social, and emotional development. Limited understanding among students regarding the forms and impacts of bullying may hinder the creation of a safe and supportive learning environment. This community service activity aimed to provide anti-bullying education to elementary school students through a socialization program conducted by students participating in the Community Service Program  KKN at UPT SDN Sumber Rame Village. The method employed consisted of three stages: preparation, implementation, and evaluation, using an educational and interactive approach adapted to the characteristics of elementary school students. The results indicated an improvement in students’ understanding of the definition, types, and impacts of bullying, as well as increased awareness of the importance of mutual respect and empathy in social interactions. Students also demonstrated high enthusiasm and active participation during the activity. It can be concluded that anti-bullying socialization through the KKN program is an effective preventive effort in supporting positive character development and fostering a safe, inclusive, and child-friendly school environment.